2008
DOI: 10.1007/s10681-008-9767-5
|View full text |Cite
|
Sign up to set email alerts
|

Mutation induction with ion beam irradiation of lateral buds of chrysanthemum and analysis of chimeric structure of induced mutants

Abstract: We compared the eVects of ion beam and gamma ray irradiation on mutation induction in axillary buds of chrysanthemum, and analyzed the chimeric structure of the resulting mutants. Axillary buds were irradiated with carbon ions at 2 Gy (mean linear energy transfer 122 keV/ m), helium ions at 10 Gy (mean 9 keV/ m), and gamma rays at 80 Gy, all of which have the similar eVects on survival. The lower Wve nodes of the shoots elongating from the irradiated buds were cut one by one, and new shoots were allowed to gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…The color change of plant tissue is one of the commonly observed phenotypes of natural mutation. The mechanisms of color change in some plants have been studied extensively (Tegopati, 2001;Li et al, 2005;Yamaguchi et al, 2009;Palai and Rout, 2011), but not in the sport varieties of the European pear. In this paper, we studied the mechanism of the formation of green-skinned MRB-G fruit and demonstrated that hypermethylation of the PcMYB10 promoter was probably the causative factor.…”
Section: Discussionmentioning
confidence: 99%
“…The color change of plant tissue is one of the commonly observed phenotypes of natural mutation. The mechanisms of color change in some plants have been studied extensively (Tegopati, 2001;Li et al, 2005;Yamaguchi et al, 2009;Palai and Rout, 2011), but not in the sport varieties of the European pear. In this paper, we studied the mechanism of the formation of green-skinned MRB-G fruit and demonstrated that hypermethylation of the PcMYB10 promoter was probably the causative factor.…”
Section: Discussionmentioning
confidence: 99%
“…In general, growth and differentiation of cultured tissues are inhibited by heavy-ion beam irradiation and the degree of inhibition increases as the irradiation dose increases (Miyazaki et al 2002;Ishii et al 2003;Okamura et al 2003;Miyazaki et al 2006;Zhou et al 2006;Godo et al 2007;Kanaya et al 2008;Sugiyama et al 2008;Sasaki et al 2008;Yamaguchi et al 2008). In the present study, growth of embryogenic calluses of both T. hirta and D. carota was also inhibited by heavy-ion beam irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy-ion beam irradiation has often been combined with tissue culture for efficient induction and selection of mutants, establishment of solid mutants from chimerical tissues and organs, and/or propagation of valuable mutants (Miyazaki et al 2002;Ishii et al 2003;Okamura et al 2003;Miyazaki et al 2006;Zhou et al 2006;Godo et al 2007;Kanaya et al 2008;Sugiyama et al 2008;Sasaki et al 2008;Yamaguchi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since the nineteenth century, they are used in horticultural production as a source of new phenotypes (Stewart et al 1972;Zonneveld 2007). Moreover, chimeras are also useful in evaluating the interactions between cells during plant development (Szymkowiak and Sussex 1996;Yamaguchi et al 2009). However, these plants are problematic in propagation and storage.…”
Section: Introductionmentioning
confidence: 99%